Can drawings help assessing dementia caregivers' burden? A preliminary study. (April 2020) - Werner, Perla; AboJabel, Hanan
The use of quantitative self-report methods for assessing the stress associated with dementia caregiving, especially among minority groups, has been lately criticized. The aim of this study was to examine whether Human Figures Drawings might provide a tool for assessing caregivers' burden. Sixty Israeli Arabs – 30 family caregivers of a person with dementia and 30 gender and age-matched non-caregivers – were asked to draw a caregiver of an elderly person with dementia and a caregiver of an elderly person with a physical disability. While no differences were found between the drawings of caregivers and non-caregivers, statistically significant differences were found between all the characteristics of the drawings depicting a caregiver of an elderly person with dementia and a caregiver of an elderly person with a physical disability, as drawn by caregivers. Several of the drawings' characteristics were significantly associated with caregiver burden. By introducing a nonverbal form of expression, Human Figures Drawings might add utility to the assessment of dementia caregivers' burden.